Seed morphology and post-seminal development of Tillandsia L. (Bromeliaceae) from the Campos Gerais, Paraná, Southern Brazil - Scatena, Vera Lucia [UNESP]; Segecin, Simone [UNESP]; Coan, Alessandra Ike [UNESP] (Brazilian Archives of Biology and Technology, 2006)
Foi estudada a morfologia da semente e do desenvolvimento pós-seminal de Tillandsia gardneri Lindl., T. streptocarpa Baker, e T. stricta Sol. ex Sims (Bromeliaceae), que ocorrem nos Campos Gerais do Paraná, Brasil. As sementes apresentaram cerca de 2,0 mm de comprimento e testa com apêndices plumosos na região micropylar. A presença desses apêndices é um caráter importante na taxonomia da família e garante sucesso na dispersão anemocórica das sementes. Após a embebição, as sementes levaram cerca de 20 dias para germinar. A primeira estrutura que emergiu durante a germinação foi o cotilédone haustorial, que é responsável pela nutrição da plântula. Eram ausentes catafilo e raiz primária. Na plântula ocorreu a formação de um pequeno tanque, que é constituído pela base da bainha da folha primária superposta à base da bainha da folha secundária. Esse pequeno tanque permaneceu na posição vertical e armazenou água e detritos orgânicos para a nutrição da plântula. As raízes adventícias emergiram tardiamente.

This work studied the morphology and post-seminal development of seeds of Tillandsia gardneri Lindl., T. streptocarpa Baker, and T. stricta Sol. ex Sims (Bromeliaceae) from the Campos Gerais, State of Paraná, Southern Brazil. The seeds (ca. 2.0 mm long) presented plumose appendages at their micropylar end, an important structure in the taxonomy of the family since it represented an elaborate apparatus allowing effective wind-dispersal. Seeds germinated after circa twenty days. The haustorial cotyledon, responsible for the seedling nutrition, appeared first during the germination process. No cataphyll or primary roots developed. A small tank came along in the seedling, formed by the base of the sheath of the first leaf, which overlapped that of the second leaf. This tank can store water and litter. The adventitious roots developed later.
Keywords: Tillandsia; seed morphology; post-seminal development